2013
DOI: 10.1038/srep02644
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Optical Coherence Tomography of Light-Driven Melanosome Translocation in Retinal Pigment Epithelium

Abstract: Optical coherence tomography (OCT) may revolutionize fundamental investigation and clinical management of age-related macular degeneration and other eye diseases. However, quantitative OCT interpretation is hampered due to uncertain sub-cellular correlates of reflectivity in the retinal pigment epithelium (RPE) and photoreceptor. The purpose of this study was twofold: 1) to test OCT correlates in the RPE, and 2) to demonstrate the feasibility of longitudinal OCT monitoring of sub-cellular RPE dynamics. A high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 36 publications
4
55
0
Order By: Relevance
“…Previous studies have shown that melanosomes translocate within the RPE under different light conditions in several types of fish 31–34 and frogs. 35,36 In the dark, melanosomes are transported to the basal end of RPE cells. However, in light, melanosomes are moved into the apical projections of the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that melanosomes translocate within the RPE under different light conditions in several types of fish 31–34 and frogs. 35,36 In the dark, melanosomes are transported to the basal end of RPE cells. However, in light, melanosomes are moved into the apical projections of the RPE.…”
Section: Discussionmentioning
confidence: 99%
“…22 Three RPE grades contain epithelial and nonepithelial components (sloughed, shedding, and intraretinal). Four are epithelial only (nonuniform, very nonuniform, bilaminar, and vacuolated).…”
Section: Discussionmentioning
confidence: 99%
“…The RPE is revealed in vivo by its abundant melanosomes, melanolipofuscin, and lipofuscin granules, all of lysosomal lineage, [23][24][25] and all potential subcellular contributors to SDOCT reflectivity. 26,27 Yet RPE imaging relies on surprisingly few data about the number, size, shape, and disposition of individual RPE cells and their organelles of imaging significance. Previous morphological studies of RPE in AMD and Stargardt disease, an inherited disorder also featuring abundant RPE lipofuscin, collectively used low-resolution light microscopy, electron microscopy of small series, minimally characterized or insufficiently advanced pathology, and imprecisely specified retinal localizations.…”
Section: Introductionmentioning
confidence: 99%